Leadership in marketing and its role in realizing service quality - A study on insurance companies on the Syrian coast- - زيود ربا; بسام زاهر (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Entrepreneurial marketing in business sectors in various fields presents a modern and advanced model, as most contemporary companies are keen to adopt it in various dimensions in their activities and in offering their products, in a way that ensures them to remain competitive in the markets, and in a way that contributes to improving individuals’ perceptions regarding the quality of the products provided, through... While adopting the most important pioneering methods related to creativity, taking advantage of opportunities, the art of dealing with risks, and creating appropriate value for customers, a descriptive and analytical approach was adopted to complete the research, and with the help of Spanish it was distributed to 350 insured individuals in insurance companies on the Syrian coast, and it became clear that there is an average reality in applying the dimensions of leadership in marketing in the companies studied, and the company’s dealing with risks was of the greatest value among the rest of the dimensions, and that there is a reality characterized by weakness in general in terms of perception of the quality of the service provided, as there is a weak feeling in terms of the security and confidence of transactions for this company, In terms of fulfilling all terms of the concluded contract and presenting obligations without evading, I also found that there is a positive correlation and a direct relationship between the dimensions of leadership in marketing and the perception of quality of service. Providing value to the customer was the most influential, followed by creativity in marketing and managing dealing with risk, and the least influential was To seize opportunities, the study recommended the necessity of emphasizing the importance of the concept of entrepreneurship and its applications, holding courses for company employees by marketing leadership specialists and how to apply it in the insurance sector, expanding the provision of services in a renewed manner, to include a wide and new segment of individuals so that they are commensurate with their risks, and continuous attention. By the company’s employees, regarding the quality of insurance and its services, and the emphasis on creating and strengthening feelings of trust and security in the hearts of the insured.